The Routledge Handbook of Buddhist-Christian studies - Anderson, Carol S.; Cattoi, Thomas (Routledge handbooks in religion, 2022)
Part I. Theory and method -- Part II. Historical encounters -- Part III. Contemporary conversations -- Part IV. Social engagement, pastoral care, and the challenge of interreligious education -- Part V. Constructive reflections.